UTILIZATION OF AGARWOOD DISTILLATION WASTE IN OILWELL CEMENT AND ITS EFFECT ON FREE WATER AND POROSITY - Arina Sauki; Muhammad Hazman Md. Shahid; Ku Halim Ku Hamid; Azlinda Azizi; Siti Khatijah Jamaludin; Tengku Amran Tengku Mohd; Nur Hashimah Alias (Chemical Engineering Diponegoro University, 2013)
The intent of this research is to utilize the waste produced by distillation process of Agarwood oil and convert it into a profitable oilwell cement additive. Common problem during oilwell cementing is free wáter separation. This problem could weaken cement at the top, gas migration problem and non uniform density of cement slurry that are even worst in cementing deviated well. Another concern on cementing design is the porosity of the hardened cement. If the cement is too porous, it can lead to gas migration and casing corrosion. All tests were conducted according to API Specification-10B. Free water test was determined at different concentrations of Agarwood Waste Additive (AWA), different inclination angles and different temperatures. Based on the findings, it was observed that zero free water was produced when 2% BWOC of AWA was used at all angles. The findings also revealed that AWA can maintain good thermal stability as it could maintain zero free water at increased temperature up to 60˚C. The porosity of AWA cement was comparable with standard API neat cement as the porosity did not differ much at 2% BWOC of AWA. Therefore, it can be concluded that the AWA is suitable to be used as an additive in oil well cement (OWC) with 2% BWOC is taken as the optimum concentration.